The minimum wage revisited in the enlarged EU (Cheltenham, 2010)
"This book provides in-depth and innovative analysis of the minimum wage in Europe. The contributing authors explore its role and scope within the enlarged EU, and address the question of whether there should be harmonization between the individual member states or even a common EU minimum wage. They also examine the impact of the minimum wage at the national level, looking at trends and effects through case studies of specific policy issues and industrial sectors. Minimum wage fixing has returned to the core of policy debates, as illustrated by the adoption of a statutory minimum wage by Austria, Ireland, and the UK and ongoing discussions in Germany and Sweden. Proposals to have common rules at the EU level have also multiplied since EU enlargement, in particular to minimize social dumping the practice of exporting goods from countries with poor labor standards. Bringing together 15 national studies from noted European specialists in the field, this timely collection aims to stimulate the current debate."